1993
DOI: 10.1017/s0022215100123874
|View full text |Cite
|
Sign up to set email alerts
|

Eye protection in ear, nose and throat surgery

Abstract: The aim of this study was to quantify the risk of blood splashes to the conjunctiva during ear, nose and throat surgery. Two hundred and sixty consecutive operations by three surgeons were assessed for contamination of safety glasses and other factors. We found that 15 per cent of operations resulted in blood droplet contamination of safety glasses. In 92 per cent of these, contaminations were on the exterior of the glasses and eight per cent were on both sides. We concluded that about one and a half per cent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 3 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…In two of these studies, the risk of conjunctival contamination of the surgeon was assessed by counting visible blood spots on goggles or safety spectacles. 7,8 The rates of blood contamination were 15 and 22 per cent, respectively. The first study included 108 tonsillectomies and found that using ties, as opposed to bipolar diathermy, for haemostasis resulted in a decreased risk of conjunctival contamination.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In two of these studies, the risk of conjunctival contamination of the surgeon was assessed by counting visible blood spots on goggles or safety spectacles. 7,8 The rates of blood contamination were 15 and 22 per cent, respectively. The first study included 108 tonsillectomies and found that using ties, as opposed to bipolar diathermy, for haemostasis resulted in a decreased risk of conjunctival contamination.…”
Section: Discussionmentioning
confidence: 98%
“…11 Just as it is important to determine the risks of different surgical procedures for patients, it is also important for surgeons to know the risks they themselves are exposed to. Although Keogh et al 8 published their results eight years after Prior et al 7 first drew attention to the risk of conjunctival contamination of the surgeon during tonsillectomy, none of the ENT surgeons surveyed by Keogh et al routinely wore eye protection during tonsillectomy, other than spectacles. Attention therefore needs to continue to be drawn to the risk of conjunctival contamination during tonsillectomy, and surgeons should be aware of which procedures or instruments place them at greater risk.…”
Section: Discussionmentioning
confidence: 99%
“…In our center, however, the endovascular treatment after failure of conservative measure is routine, which emerged also from the discussion with our otorhinolaryngologists. It has been investigated that there is a high risk of contamination of medical staff with patient`s blood during surgery [27,28]. Since we are frequently asked to treat epistaxis, we developed a protocol with high safety standards to avoid CVA.…”
Section: Discussionmentioning
confidence: 99%
“…[10] Inoculation of the conjunctiva by the patient's blood may cause transmission of HBV, HCV, and HIV infections [11,12] and this may occur while performing tonsillectomy procedure. [13][14][15] Lakhani et al [10] examined the degree and incidence of blood splashes in otolaryngology procedures performed in their unit for 12 weeks. They wore a mask with a visor and examined the masks for blood splash.…”
Section: Discussionmentioning
confidence: 99%